Dissolution kinetics of pH responsive alginate-pectin hydrogel particles. (October 2016) - Guo, Jingxin; Kaletunç, Gönül
Abstract: Encapsulation is used for protection of bioactive compounds during processing, storage, and passage through the upper gastrointestinal (GI) tract and delivery to the small intestine. A number of pH responsive synthetic polymers are approved for drug delivery but are not allowed for food applications. We developed a biopolymer mixture composed of alginate and pectin that can form hydrogel when the pH is below 3.0. We also produced novel disc shaped particles which can potentially enhance the particle adhesion in intestines. As the pH increases, Al-P hydrogels go through a gel-sol transition and the dissolution kinetics of the hydrogel dominates the bioactive compound release. The goals of this study are to investigate the relative effects of factors contributing to the dissolution kinetics of Al-P hydrogel and to develop mathematical models characterizing the degradation behavior of the hydrogels under product storage and lower GI tract conditions. The volume change of spherical and disc shaped particles at pH 3.0 showed that the hydrogel particles would be stable in low pH beverages during storage. At pH 5.0 and 7.0, hydrogel particle dissolution followed a zero-order kinetic model. The 2.8% TGC 43:57 wt% Al-P disc particles had the fastest and the 2.2% TGC 82:18 wt% Al-P spherical particles had the slowest volume dissolution rate at pH 7.0 and 37 °C. Activation energies of hydrogel particles were significantly affected by pH, particle shape and Al to P ratio. Such a biopolymer system which responds to pH provides an opportunity to use food as a vehicle for targeted delivery of bioactive compounds. Highlights: Alginate-pectin (Al-P) formed hydrogel at pH 3.0 and below. Hydrogel particle shape depended on Al to P ratio, drop distance and flow rate. Al-P hydrogel was dissolved in pH higher than 5.0 and stable in pH 3.0. Al to P ratio, particle shape, temperature and pH affected hydrogel dissolution rate.